A technology integration approach for optimising biohydrogen production from food waste - Okoro-Shekwaga, Cynthia Kusin; Wilmshurst, Mark (Frontiers in Fuels, 2024)
The present study proposes a novel approach of combined inoculum and food waste heat shock pretreatment for biohydrogen production through dark fermentation. It evaluates the effect of the heating duration (at 115 ̊C) and starting pH on the biohydrogen yield and system profiles in two stages, namely Exp1 and Exp2. Exp1 investigated the optimal heating duration and starting pH for a combined inoculum/food waste heat shock pretreatment. A 24-hour biohydrogen production test at four heating durations (15, 30, 45 and 60 minutes) was assayed at acidic and alkaline starting pH ranges (4, 5, 6 and 8, 9, 10). The optimal starting pH from these experiments across all four heating durations was pH 5. An optimal level was not reached for the assayed heating durations. Biohydrogen yield increased linearly from 37.4 to 63.8 mL/gVS, with an increase in heating duration from 15 to 60 minutes at pH 5. Therefore, additional tests were conducted at pH 5 for extended heating durations of 75 to 120 minutes. Biohydrogen yield was similar at 75, 90 and 105-minute heating durations in a range of 69.7 to 73.5 mL/gVS. Above 105 minutes of heating duration, the overall gas production starts to decline, making it the maximum allowable heating duration. In Exp2, a comparative analysis of the system profiles between the combined inoculum/food waste pretreatment (Test) and inoculum-only pretreatment (Control) was investigated using the optimal heating duration range (75 and 105 minutes) and starting pH of 5. The peak biohydrogen yield from the Control was achieved following a 75-minute heating duration (84.5 mL/gVS, 58.6%), while this was achieved following a 90-minute heating duration for the Test (81.3 mL/gVS, 53.3%). Higher volatile fatty acids fermentation and pH recovery were achieved in the Test in addition to potential economic savings compared to the Control. This is particularly important where anaerobic digestion is deployed for downstream effluent processing. Therefore, this innovative approach of combined food waste/inoculum heat shock pretreatment presents opportunities to integrate dark fermentation into existing anaerobic digestion systems as a step to scale up the dark fermentation technology from lab to real-life application.